الشقاء الإنساني في روايات مختارة لنجيب محفوظ وعبد الصمد سعيد :b - Muhd Zulkifli bin Ismail
This thesis contains an analytical and comparative study of the manifestations of human misery in selected novels of two writers, namely, the Egyptian novelist Naguib Mahfouz and the Malaysian Malay novelist A. Samad Said. The selected novels are al-Qahirah al-Jadidah, Zuqaq al-Midaqq and Bidayah wa Nihayah by the former and Salina, Sungai Mengalir Lesu and Di Hadapan Pulau by the latter. By misery is meant the material and psychological sufferings endured by a human being in his life such poverty, starvation and anxiety. The study aims to analyse the writers' vision regarding the relationship between this misery and the notion of shaqa' (wretchedness) as understood in Islam. The researcher discussed the concept of shaqa' in Islam and came to a conclusion that it is fundamentally related to the abandonment of the divine guidance and non-compliance with the lifestyle it ensues. To accomplish his objective, the researcher then sifted out the manifestations of misery that were depicted by the two novelists in the selected novels and present them in relation with the characters of the novels. Accordingly, an analysis was carried out to ascertain the extent to which this form of misery bears a relationship to the abandonment of the divine guidance based on the writers' vision. Following that, the artistic achievement of both novelists in that respect was discussed and this study has managed to show their skillfulness in using the tools of the genre appropriately according to the contexts of the situations. This, in the end, explains the reason why their works have reached such a high standard of literary achievement.